MicroRNA in vitro diagnostics using immunoassay analyzers - Kappel, Andreas; Meder, Benjamin (Clinical chemistry, 2015)
BACKGROUND: The implementation of new biomarkers into clinical practice is one of the most important areas in medical research. Besides their clinical impact, novel in vitro diagnostic markers promise to have a substantial effect on healthcare costs. Although numerous publications report the discovery of biomarkers, only a fraction of those markers are routinely used. One key challenge is a measurement system that is compatible with clinical workflows. METHODS: We designed a new immunoassay for microRNA (miRNA) quantification. The assay combines streptavidin-linked microparticles, a biotinylated catcher oligonucleotide complementary to a single miRNA species, and finally, a monoclonal antibody to DNA/RNA heterohybrids labeled with acridinium ester. Importantly, our assay runs on standard immunoassay analyzers. After a technical validation of the assay, we evaluated the clinical performance on 4 Alzheimer disease miRNAs. RESULTS: Our assay has an analytical specificity of 99.4% and is at the same time sensitive (concentrations in the range of 1 pmol/L miRNA can be reliably profiled). Because the novel approach did not require amplification steps, we obtained high reproducibility for up to 40 biological replicates. Importantly, our assay prototype exhibited a time to result of <3 h. With human blood samples, the assay was able to measure 4 miRNAs that can detect Alzheimer disease with a diagnostic accuracy of 82% and showed a Pearson correlation >0.994 with the gold standard qRT-PCR. CONCLUSIONS: Our miRNA immunoassay allowed the measurement of miRNA signatures with sufficient analytical sensitivity and high specificity on commonly available laboratory equipment.